Learning vocabulary for IELTS Academic Reading: An evaluation of some pedagogical materials - Marta Serrano (Universitat Jaume I. Department of English Studies, 2020)
A large receptive vocabulary could have a significant impact on scores in the IELTS Academic Reading test. However, the lack of official information about vocabulary in this test raises questions regarding how lexis is selected and approached in existing IELTS training materials. This paper evaluates three books issued by leading ELT publishers to assess how far they effectively help learn vocabulary for the Academic Reading test. First, the lexis in the test is identified based on what can be gleaned from official information and available research. Then, the three books are evaluated using a checklist of criteria relevant to the acquisition of this lexis. The results suggest that the materials investigated may not contribute enough towards the acquisition of vocabulary useful for success in the Academic Reading test. This paper offers some important insights into some shortcomings of current IELTS training materials and points to ways of surmounting them.